Analisis Konsep Kinerja Keuangan Bank Mega Syariah Periode 2022-2023 - Nasution, M. Hafis Akbar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of writing this thesis is to analyze whether the financial performance measured using the financial ratio of PT Bank Mega Syariah in 2022-2023 has increased. The analytical tool used in this study is the Financial Ratio. The results of the study indicate that in the period 2022-2023 when measured from the analysis of the Profitability ratio Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) of PT Bank Mega Syariah in 2023 increased while BOPO decreased in 2023. When viewed from the Liquidity ratio, it shows that the Quick Ratio, Financing To Deposit in 2023 decreased in 2020. Meanwhile, with the Solvency Ratio Analysis, it can be seen from the Risk Asset Ratio (RAR) which increased in 2023 while the Primary Ratio (PR) decreased in 2023.